STAGES OF ECONOMIC DEVELOPMENT OF THE COUNTRY'S AGRICULTURE AND ITS INSTITUTIONAL CONDITIONS - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article describes the institutional conditions for the development of the agricultural sector in the country, the reforms carried out in agriculture and the stages  of  agricultural  development.  The  article  also  analyzes  the  development  of agriculture in the country using research methods. The first stage of development is the period up to the nineties of the last century, when the activities of artel, commune, chorikor, collective and state farms were carried out, the second stage is the period from  1994  to  2004,  when  the  state's  rational  policy  and  financial  support  for agricultural  enterprises  led  to  the  normalization  of  the  agricultural  situation  in  the country, the third stage is the period of active growth from 2004 to 2017, and the fourth stage  is  the  period  of  transition  from  raw  materials  to  the  production  of  finished products in agriculture (clustering), which has been ongoing since 2017. The article also analyzes the development of agriculture in stages using research methods. The first stage of development is the period up to the nineties of the last century, when the activities of artel, commune, chorikor, collective and state farms were carried out, the second stage is the period from 1994 to 2004, when the state's rational policy and financial support for agricultural enterprises were achieved, the third stage is the period of active growth from 2004 to 2017, and the fourth stage is the period of transition from  raw  materials  to  finished  products  (clustering),  which  is  being  discussed  in organizational, economic and regulatory legal terms.